Gait Pattern, Impact to the Skeleton and Postural Balance in Overweight and Obese Children: A Review - Nili Steinberg; Dan Nemet; Michal Pantanowitz; Alon Eliakim (MDPI AG, 2018)
The article reviews the biomechanical factors that may cause overweight/obese children to reduce their level of physical activity, while increasing their risk of overuse injuries and exercise-related pain. Recommendations would be to screen those children for any gait or postural impairments before they join any exercise program, and to provide them with specific gait treatments and/or physical exercise programs, in order to decrease their risk for future musculoskeletal injuries and pain.